School Management Analysis Indonesian Towards School Supervisors Quality of Education Better in the Disruption Era 4.0 - Manurung, Paisal; Bayu, Eka Pasca Surya; Theresia, Monica (International Journal for Educational and Vocational Studies, 2020)
This paper explains the quality of school management in dealing with the condition of school supervisors at the level of the education unit in the region. Supervisors in the education unit are part of the management which is often considered a form of work of the school leadership in managing and managing everything that is connected with the administration of the students. For the success of school management conditions in the face of an era of disruption 4.0, schools must correct the failure of management, becoming better management. These will be important in maintaining the quality of education management and the quality of education itself as the desired management of the law to educate the nation's life.